Simulation research on operation scheme of dissymmetrical main engine of CODOG propulsion system - HUANG Bin (Zhongguo Jianchuan Yanjiu, 2018)
[Objectives] How to maintain propulsion capability in a CODOG propulsion system damage situation has important significance. [Methods] A ‘Hull-Engine-CPP-Rudder’ simulation model of a CODOG marine power plant is established on Simulink using the modularized method, and a dissymmetrical main engine urgent working mode is proposed and simulated. [Results] The results show that in the dissymmetrical working mode, two different engines cannot work simultaneously at designed capacity. However, by adjusting the pitch of the CPP, one engine can work at designed capacity and the other can work at partial load capacity; under this working mode, if high speed is demanded, the gas turbine should work at designed capacity. The CPP pitch driven by diesel should be maintained at a high value near the maximum. The maximum speed of this working mode is 84.4% of the designed speed, which is higher than the speed of the single shaft working mode driven by a gas turbine. [Conclusions] The research results of this paper can provide useful references for the design of ship propulsion systems.